Potensi Tradisi Grebeg Dalam Meningkatkan Kunjungan Wisatawan Daerah Istimewa Yogyakarta - Cikal Nursalam; Eka Syahputra (Gemawisata: Jurnal Ilmiah Pariwisata, 2023)
Tourism is a sector in Indonesia that plays a role in the economy by increasing people's incomes, increasing and leveling employment opportunities, and serving as a source of foreign exchange. However, as a tourist destination, Yogyakarta is experiencing lagging problems in increasing tourist visits. The Grebeg tradition is part of the culture in Yogyakarta as a community celebration to commemorate an event. This research aims to examine the potential of the Grebeg tradition in Yogyakarta to increase tourism in Indonesia. Based on the results of this research, the Grebeg tradition can become part of potential tourism in Yogyakarta and a means of entertainment for local tourists to create knowledge of cultural heritage and love for the Indonesian nation.